Short-term tocolytics for preterm delivery – current perspectives - Haas, David M (Dove Medical Press, 2014)
Administration of short-term tocolytic agents can prolong pregnancy for women in preterm labor. Prolonging pregnancy has many benefits because it allows for other proven interventions, such as antenatal corticosteroid administration, to be accomplished. This review provides an overview of currently utilized tocolytic agents and the evidence demonstrating their efficacy for prolonging pregnancy by at least 48 hours. General pharmacological principles for the clinician regarding drugs in pregnancy are also briefly discussed. In general, while the choice of the best first-line short-term tocolytic drug is not clear, it is evident that use of these agents has a clear place in current obstetric therapeutics.